Resolving Conflicts using Indigenous Institutions: A Case Study of Njuri-Ncheke of Ameru, Kenya - Mburugu, Kirema N.; Macharia, David (My University, 2016)
The history of conflict is as old as human history. From the dawn of human history, communities have been competing for control of resources and for dominance. These competitions inevitably led individuals as well as social, political, economic, and religious groups to conflicts. It is true that conflict has devastating effects and it is unwanted. It is also true that conflict is unavoidable and it continuous to occur. Conflict is a natural phenomenon in human society except that the approach to its perceptiveness, nature and management vary from society to society. Even the patterns and phases of conflict vary from community to community. Since the causes of conflict are different, it would be better to use different mechanisms for the prevention and resolution of conflicts. This study sought to assess the role of indigenous institutions in promoting sustainable peace in Kenya. The study aimed at exploring the methods used by indigenous institutions in conflict resolution, their achievements, constraints and how to strengthen their role in promoting sustainable peace in the country. A case study of Njuri Ncheke Council of elders of Ameru was taken. The Council has its headquarters at Nchiru market about 13 kilometres from Meru Town. Njuri Ncheke has a membership of approximately five thousand elders who are spread in the current two Meru counties, that is Meru and Tharaka/Nithi counties. Johan Galtung’s conflict theory and analysis that seeks to understand the root causes of conflicts, structure and dynamics of conflicts and its actors with an aim of suggesting possible resolution strategies was used. It reflects the general theory that violence is inevitable and the aim of peace action should therefore be preventing, managing, limiting and overcoming violence. The study used descriptive survey design and research instruments used were questionnaires and interview schedule. Descriptive statistics were used to present the findings of the study. The study revealed that Njuri-Ncheke is involved in conflict resolution and promotion of peace in Meru community. Most of the conflicts are resolved at Njuri-Ncheke houses with only intra NjuriNcheke disputes and appeals getting handled at Njuri-Ncheke headquarters. The conflict resolution methods used by Njuri-Ncheke council of elders included determination of cases, oathing, counseling, peace crusades, dialogue and instilling discipline among community members.
Keywords: Conflict; indigenous institutions; sustainable peace